Exploring Place Attachment in the Traditional Shopping Area of Misurata City, Libya (مجلة البحوث الأكاديمية, 2025)
This study investigates the role of place attachment in shaping the experiences of individuals in the traditional shopping area of Misurata City, Libya. Using a qualitative approach, site observations and semi-structured interviews were conducted with 24 participants to explore the factors influencing place attachment in this context. The results reveal three key themes: walkability; mixed-use and active frontages; and attractiveness and pleasantness. The findings suggest that the traditional shopping area is a vibrant and walkable space that fosters social interactions and a sense of community. The study highlights the importance of designing urban spaces that prioritize walkability, active frontages, and social interaction to promote place attachment and enhance the overall quality of life for residents. The findings have implications for urban planning and design, and contribute to the growing body of research on place attachment and its role in shaping urban environments.